A Study of the Relationship Between Teachers’ Leadership Capacity and Teachers’ Decision-Making Styles in Gangbei Construction Primary School， Guigang, Guangxi Province, China - Zhang, Xinyi; Watana Vinitwatanakhun (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Keywords: Teacher, Teachers’ leadership capacity, Teachers’ decision-making styles. The study is carried out to explore the relationship between teachers’ perceptions of their leadership capacity and their decision-making styles in Gangbei Construction Primary School. 112 full-time teachers from the academic year of 2021, Gangbei Construction Primary School are included in the survey. The analytical statistic was Mean and Standard Deviation and Pearson Product-moment coefficient. The result shows the main purpose of the study is to examine the relationship between teachers’ leadership capacity and their decision-making styles. The study found that “teacher’s leadership capacity” and teachers’ decision-making styles” were significantly correlated, r = .95, p = < 0.01. The Pearson Correlation test indicated that there was an obvious relationship between teachers’ perceptions of their leadership capacity and their decision-making styles in the Gangbei Construction Primary School in Guigang, Guangxi Province, China.